2019
DOI: 10.1371/journal.pone.0221868
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota and their putative metabolic functions in fragmented Bengal tiger population of Nepal

Abstract: Bengal tigers ( Panthera tigris tigris ) serve a pivotal role as an apex predator in forest ecosystems. To increase our knowledge on factors impacting the viability and health of this endangered species, we studied the gut microbiota in 32 individual Bengal tigers from three geographically separated areas (Chitwan National Park (CNP), Bardia National Park (BNP) and Suklaphanta Wildlife Reserve (SWR)) in Nepal, using noninvasive genetic sampling methods. Gut microbiota influence the immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 81 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have described the gut and fecal microbiota of the tiger [He et al, 2018a, b, c;Karmacharya et al, 2019]. However, the members of the microbial community of the tiger after birth remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described the gut and fecal microbiota of the tiger [He et al, 2018a, b, c;Karmacharya et al, 2019]. However, the members of the microbial community of the tiger after birth remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These major phyla, Fusobacteria , Firmicutes , Bacteroidetes , Proteobacteria , and Actinobacteriota , which occupied the gut microbiome of SC, were also found in the other two subspecies of tigers, Amur tigers, and Bengal tigers, which are captive in the same zoo as SC is ( Supplementary Tables 3 , 4 ). The same phyla were also reported to occupy the gut microbiome of captive Amur tigers in the northeast of China ( He et al, 2018 ; Ning et al, 2020 ) and Bengal tigers living in Nepal ( Karmacharya et al, 2019 ). Both this study and a study of the gut microbiome of tigers captive in a zoo in Southern China conducted by Jiang et al found that Firmicutes was the major phylum of these three subspecies of tigers ( Jiang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 79%
“…As previously reported, Acidobacteria and Verrucomicrobia were not found in the fecal microbiota of lions ( Mittal et al, 2020 ), tigers ( He et al, 2018 ; Ning et al, 2020 ), and snow leopards ( Zhang et al, 2014 ). Both Acidobacteria and Verrucomicrobia contain enzymes that encode cellulose and hemicellulose and are involved in plant degradation ( Kanokratana et al, 2011 ; Chen et al, 2017 ; Karmacharya et al, 2019 ). We speculate that a certain proportion of Acidobacteria and Verrucomicrobia in Panthera animals’ fecal samples may be related to their prey ( Grieneisen et al, 2019 ; Mittal et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%